Evaluation of Different Techniques of Working Length Determination in Comparison with CBCT - Anubha Srivastav; Ramesh Chandra; Shazia Siddiqui; Divya Chowdhary; Alpana Katiyar; Rehan Ahmad Khan (Indian Journal of Dental Research)
Aim: To estimate the working length of teeth using conventional tactile technique, radiovisiography technique, Apex locator, and confirmation of working length by cone beam computed tomography technique. Materials and Methods: Forty patients with the age group between 20 and 50 years with irreversible pulpitis were included in this study. After taking a preoperative radiograph, the procedure was started. The cavity wall buildup was done using composite in the cases needed and then rubber dam application was done. The working length of mesiobuccal and mesiolingual canal was taken using cone beam computed tomography and this was considered as the standard value. Then using tactile method, length of the canal was measured using radiovisiographic software followed by apexlocator. Result: The Apex locator has showed best result as compared to tactile and radiovisiography. Conclusion: Apex locator values were closest to cone beam computed tomography working length measurement values and electronic apexlocator can be used efficiently as an alternative method for working length determination. The quality of various techniques according to ranks of working length determination was found to be Cone beam computed tomography (CBCT) > Apexloc > Radiovisiography (RVG) > Tactile. Thus, Apex locator can be used as an alternative to cone beam computed tomography for working length determination.